Analisa Usability Pada Website Pengadilan Agama Ujung Tanjung Menggunakan Metode User Centered Design - Sri Rahayu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The website of the Ujung Tanjung Religious Court (PAUTJ) is a website used to access information about the Ujung Tanjung Religious Court. Since the creation of the PAUTJ website until now, no one has conducted research on usability and design on this PAUTJ website. As a result, an evaluation must be conducted on the PAUTJ website to assess the usability aspect of its user interface. The purpose of this study is to evaluate the website from a design and usability perspective and develop a prototype design proposal. In this study, the User Centered Design (UCD) method uses two stages, and the Quality In Use Integrated Measurement (QUIM) method uses ten variables to calculate the usability value. Data collection was carried out by sending questionnaires through Google forms to 100 PAUTJ website users. This study found that 73% of the QUIM data calculations showed that the website of the Ujung Tanjung Religious Court was in the good category; however, the study found that there are four points of improvement needed to make users feel satisfied when using the PAUTJ website. These improvements are demonstrated in the proposed UI design, which can be used as a reference for subsequent website development